A survey on relationship between capital structure, free cash flow and diversification and firm performance of listed companies in Tehran Stock Exchange - Mohammad Khodaei Valahzaghard; Maryam Borzabadi Farahani (Management Science Letters)
This paper presents an empirical investigation to study the effects of free cash flow, share diversification and capital structure on Tobin-Q in selected firms on Tehran Stock Exchange. The population of the survey includes 520 firms listed on this exchange until year 2012 and the survey uses a sample of 105 firms, randomly. The study uses the models originally developed by Palepu (1985) [Palepu, K. (1985). Diversification strategy, profit performance and the entropy measure. Strategic Management Journal, 6(3), 239-255.] to measure the effects of different factors on Tobin Q. The study has indicated that while capital structure and free cash flow influence positively on Tobin Q, diversification has maintained a negative and meaningful relationship with Tobin Q.